Risky business: policy uncertainty and investment - Giacomo Brusco; Benjamin Glass (International Tax and Public Finance, 2022)
Previous work has shown that nonlinear taxation can affect the willingness to undertake risky investments. We show that similar results can arise if agents are uncertain regarding future tax rates. Uncertain taxes distort investment decisions when tax rates are correlated with marginal productivity. We demonstrate this result in a simple theoretical framework, which can also explain some well-known results on the effects of tax progressivity and tax asymmetry on investment. Time-series estimates for the post-WW2 era suggest a negative correlation between effective tax rates and total factor productivity in the USA, yielding an effect on firm investment equivalent to an investment subsidy of around 1 percent. Our results have wide-ranging implications for a variety of tax-related work, including effective tax rates, optimal audit policy, and principal-agent problems between investors and managers.
Keywords: H21; H25; H26; H30; H31; H32; 340; Policy uncertainty; Investment; Tax asymmetry; Tax progressivity; Taxation asinsurance; Audit policy; Effective tax rate